Indonesian Students' Psychological Well-Being in Istanbul, Turkey - Azam Syukur Rahmatullah Rahmatullah; Muhammad Azhar; Siti Marpuah (Universitas Islam Tribakti Lirboyo Kediri, 2022)
This qualitative study aims to determine and analyze Indonesian students' psychological well-being in Turkey. In addition, it is intended to explore students' experiences when studying in Turkey and reveal what and how vigorous efforts were made to adapt to a new country. The research approach used was phenomenology, which pays more attention to the individual's subjective experience. The researchers then interviewed students who had just lived in Turkey for one year and students who had been in Turkey for more than one year. Hopefully, it could be explored more in aspects of the psychological well-being of students studying in Turkey. The study results highlighted that several elements affected students' psychological well-being during the adaptation period in Turkey, including different food, a quite complicated language to learn, different weather, association with international students, and not easy adaptation on campus. Furthermore, self-defense efforts to stay strong and motivated by new students in Turkey comprised of holding motivational halaqah, visits (monitoring) to new students' residences, maximizing WhatsApp groups, and bringing in motivators from outside.